2022
DOI: 10.1177/02537176221086983
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related Stigma Among the Affected Individuals: A Cross-Sectional Study From Kerala, India

Abstract: Background: The studies and case reports from various parts of the world are showing discrimination and stigma associated with COVID-19. Stigma can directly worsen the mental health of people and also worsen physical health indirectly. This study is aimed to assess the anticipatory and experienced stigma associated with COVID-19 in affected individuals. Methods: This was a cross-sectional study conducted at Palakkad District in Kerala. Study participants were patients diagnosed with COVID-19. The sampling meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The most common was social isolation. 16,17,1921,3335,37,39,41,42,44,47,48,53,56,57,60,73,76,88 In 16 studies blaming from others was the second most common social stigma reported due to being infected with COVID-19. 22,23,39,40,46,48,5155,60,62,72,83,89 In 13 studies, participants experienced rejection from the social environment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most common was social isolation. 16,17,1921,3335,37,39,41,42,44,47,48,53,56,57,60,73,76,88 In 16 studies blaming from others was the second most common social stigma reported due to being infected with COVID-19. 22,23,39,40,46,48,5155,60,62,72,83,89 In 13 studies, participants experienced rejection from the social environment.…”
Section: Resultsmentioning
confidence: 99%
“…22,23,39,40,46,48,5155,60,62,72,83,89 In 13 studies, participants experienced rejection from the social environment. 29,33,37,44,46,47,50,56,60,73,76,80,83 Other stigmas experienced by COVID-19 patients included psychological pressure, 62,6672,75,79,81 verbal violence, 20,5052,55,56,59,61,77,83 avoidance, 2224,26,4042,47,54 labeling, 17,19,21,23,27,29,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations